Effect of Different Larval Diets on Life History Traits and Nutritional Content in Anastrepha fraterculus (Diptera: Tephritidae) - Fernández, Fátima Liliana (2025)
Anastrepha fraterculus (Diptera: Tephritidae) is a major fruit pest in several countries of South America and is mass-reared for use in integrated pest control strategies, including the sterile insect technique (SIT), and as a host for rearing biocontrol agents. Optimizing these rearing protocols requires a deeper understanding of how larval diet impacts adult traits. This study investigated the effects of three larval diet formulations differing in nutrient composition on larval development and adult fitness traits. All diets contained inactive non-hydrolyzed brewer’s yeast and sucrose. Two of them included wheat germ,either alone (wheat germ diet) or combined with mashed carrot (carrot diet), whereas the corn flour diet did not contain wheat germ. The carrot diet produced the heaviest pupae, adults with longer wings, and the lowest rate of deformed adults. The corn flour diet prolonged larval and pupal development and increased adult lipid and carbohydrate content. Both the corn flour and carrot diets led to greater glycogen accumulation and more skewed weight distributions compared to the wheat germ diet. Present results highlight howlarval diet composition determines developmental traits with direct consequences on adult physiology in A. fraterculus. These characteristics could enhance the effectiveness of control programs such as SIT and other biological control strategies.